Pengaruh Penyuluhan Tentang Imobilisasi Terhadap Pencegahan Hematom Pasca Cathetirisasi Jantung Penelitian Quasi Eksperimen DI RSU Dr. Soetomo Surabaya - Kurniawati, - (2004)
Promotion is important in creating behavioral change, including immobilization, in the occurrence of post-cardiac catheterization hematoma. To .fmd the effect of promotion on immobili7.ation towards the occurren•ce of of postcardiac catheterization hematoma, a study was carried out in Cardiovascular lntervension Diagnostic Installation (CID1), Dr SoetQmo Hospita~ Surabaya, from June 14 to 1 uly 19, 2004. This was a quasi-experimental study using post-test only control group design. Population was all post-cardiac catheterization patients treated at CIDl, Dr Soetomo Hospital, Surabaya. The samples comprised totally 20 respondents, 10 as control group, and the remaining 10 as treatment group. Samples were recruited using purposive sampling. The independent variable was health promotion on immobilization in post-cardiac catheterization, and the dependent variable VI'3S the occurrence of hematoma. Data collection was carried out using questionnaire and observation the respondents who receiving and not receiving promotion. Data were analyzed with SPSS using Mann-Whitney Test for two independent samples with significance level of p ~ 0.05. Results revealed that the average rank value of control group was 7.50 (Wx = 75,000), and that of the treatment group was 13.50 (Wy = 135,000). The estimated Z value was 2.669 with significance probability of 0.008. Conclusively, health promotion has effect on the occurrence of post-cardiac catheterization hematoma.